ҚАРАҚАЛПАҚ ХАЛЫҚ ЕРТЕКЛЕРИ ТИЛИНДЕГИ ЖӘМИЙЕТЛИК – СИЯСИЙ ТАРИЙХЫЙ СӨЗЛЕР - Кунназарова, Ш.М. (ILIM hám JÁMIYET, 2017)
The article deals with outdated words used in folk tales. There are given lexemes from outdated words concerning socio-political life,features of their usage on the material of concrete examples.